The Telemark Breast Score: A Reliable Method for the Evaluation of Results after Breast Surgery. Issue 3 (September 2016) - Begic, Anadi; Stark, Birgit
Abstract : Background: Validated instruments for assessing results after breast surgery are sparse. The authors present here a method used for the past 10 years at their institution for evaluation of outcome after breast-conserving surgery and microsurgical breast reconstruction. Methods: The Telemark Breast Score is a method based on standard two-dimensional photographs assessing the outcome after breast surgery in terms of volume, shape, and symmetry. Three panels comprising two plastic surgeons, two breast surgeons, and two nurses tested the Telemark Breast Score on 346 patients who underwent breast-conserving surgery for cancer and 31 other patients who underwent deep inferior epigastric perforator flap reconstruction. All patients were assessed at least 1 year after their operation. Consistency of agreement between and within the panels was studied. Results: Interobserver and intraobserver reliability was good after consensus discussion. Good rating stability was shown using test-retest measurements. Conclusion: The Telemark Breast Score is an inexpensive, statistically reliable method and can be applied for quality control after breast surgery. CLINCAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.